HSP90, a Capacitor of Behavioral Variation. - Hung, H.C.; Kay, S.A.; Weber, F. (Journal of Biological Rhythms, 2009)
Many aspects of behavior such as aggression, courtship, sexual orientation, and the sleep-wake cycle are determined by specific genes. Although point mutations in these genes predictably change characteristics of behavior, substantial variation can be observed among a population as well as during the lifetime of individuals. The origin of variation in behavior, however, is largely unknown. Here the authors investigated the role of HSP90 for the circadian control of behavior in Drosophila. They found that a partial loss of HSP90 function, either by mutagenesis or by pharmacological inhibition, did not affect the circadian clock itself, but the translation of molecular oscillations into behavioral rhythms. In HSP90-deficient flies behavioral activity was no longer stringently coupled to molecular oscillations giving rise to a large variation in individual behavioral activity patterns. The results show that HSP90 is a potent capacitor of behavioral variation, analogous to its role in morphology. Decreased HSP90 activity not only increases behavioral variability among a population, but interestingly also during the lifetime of individuals.